Investigation of β defensin gene expression in the ocular anterior segment by semiquantitative RT-PCR - Lehmann, O. (2000)
AIM—To determine if β defensins are expressed in the anterior segment of the eye and to determine the temporal pattern of expression using a real time semiquantitative reverse transcription polymerase chain reaction (RT-PCR). METHODS—Ocular tissue (corneal epithelium, conjunctiva, iris, and lens capsule) was collected from 23 patients undergoing surgery. Serial corneal or conjunctival impression cytology was performed on a separate group of 10 patients undergoing corneal tunnel phacoemulsification or trabeculectomy. The samples were analysed for β defensin mRNA by semiquantitative RT-PCR and the mRNA standardised for cell numbers. RESULTS—RT-PCR amplified β defensin 1 mRNA from all lens capsule (six) and corneal (five) samples and all but one of the conjunctival (six) and iris samples (six). β Defensin 2 mRNA was amplified from three of five corneal, two of six conjunctival, and none of the iris or capsule samples. The impression cytology samples demonstrated a decline in defensin expression over the three time points studied. There were no false positive results from either the no-RT or negative control samples. CONCLUSIONS—This preliminary study confirms that natural antibacterial peptides are expressed in the anterior segment of the eye. There appears to be a pattern to the expression with inducible β defensin 2 not expressed intraocularly and higher levels of β defensin 1 than β defensin 2 expressed in extraocular tissue. The implication is that β defensin 1 is constitutively produced in ocular tissues and represents a key component of the innate immune system.